Analisis Morfosemantik Nama Anak Indonesia Kontemporer yang Dipublikasikan secara Publik di Media Sosial Digital (2025–2026): Morphosemantic Analysis of Contemporary Indonesian Children Names Published on Digital Social Media (2025–2026) - Batubara, Nisa Anggraini; Dilla, Frisca; Yuliarti, Yuliarti (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study examines the morphosemantic patterns of contemporary given names in Indonesia, focusing on births publicly announced between January 2025 and March 2026. Framed within socio-onomastics (Aldrin, 2019) and derivational morphology (Lieber, 2021), this research aims to identify the morphological composition and semantic domains that reflect shifting parental aspirations in a globalized, digitally connected society. The corpus comprises 30 given names purposively sampled from verified digital platforms, including national online news portals, public Instagram accounts, and TikTok announcements. Employing a qualitative descriptive method, the analysis identifies morphological structures (monomorphemic vs. polymorphemic compounds), etymological sources, and semantic fields based on referential and connotative meanings. Findings reveal a predominance of polymorphemic compounds (three to five constituents) formed through cross-linguistic compounding, predominantly blending Arabic, Sanskrit, and Western lexical elements. Semantically, five dominant clusters emerge: religiosity, leadership/intellect, aesthetic beauty, wisdom, and aspirational uniqueness. Notably, a significant subset exhibits phonological neologisms (e.g., Perfexio, Clairose), indicating that phonetic aesthetics and distinctiveness are increasingly prioritized over transparent etymological meaning. However, this study explicitly acknowledges its limited generalizability due to the small sample size and urban-digital demographic bias. Nevertheless, the findings offer preliminary insights into how linguistic hybridization and morphological creativity are reshaping Indonesian onomastic traditions within digitally mediated public spheres.